Censo aéreo invernal de aves playeras en la costa de Sonora, México (invierno 2016-2017) - Carmona, Roberto; Águila, Sergio Noé; Vidal, Sharin; Carmona-Islas, Cynthia; Danemann, Gustavo (Instituto de Ecología, A.C., 2020)
We evaluated the importance of Sonoran coastal lagoons for wintering shorebird by carrying out in February 2017 aerial surveys in 13 of the largest lagoons. We recorded 400,716 shorebirds, 70% corresponded to the southern portion, 9% to the middle portion and 21% to the north of the state. The three most important bays in numbers and percentages of shorebirds were Tóbari (127,570 records, 32%), Yavaros-Moroncarit (86,469 records, 21%) and Lobos (55,684 records, 14%). Other places with important abundances were San Jorge Bay (34,768 records, 9%), Santa Clara (18,769 records, 5%) and Colorado River's Delta (20,184 records, 5%). By size, small (15-22cm) and big (33cm or bigger) shorebirds abundances were similar (48% y 43%, respectively), medium size (23-32cm) shorebirds were uncommon (8%). Abundance ranks Sonora between the three most relevant states in Mexico for wintering shorebirds (along with Baja California Sur and Sinaloa).